The Global Prevalence of Bacillus spp. in Milk and Dairy Products: A Systematic Review and Meta-Analysis - Tianmei Sun; Ran Wang; Yanan Sun; Xiaoxu Zhang; Chongtao Ge; Yixuan Li (Foods)
The spoilage of dairy products and foodborne diseases caused by Bacillus spp. are important public concerns. The objective of this study was to estimate the global prevalence of Bacillus spp. in a range of milk and dairy products by using a meta-analysis of literature data published between 2001 and 2023. A total of 3624 publications were collected from Web of Science and PubMed databases. Following the principles of systematic review, 417 sets of prevalence data were extracted from 142 eligible publications. Estimated by the random-effects model, the overall prevalence of Bacillus spp. in milk and dairy products was 11.8% (95% CI: 10.1–13.7%), with highly severe heterogeneity (94.8%). Subgroup analyses revealed substantial heterogeneity in Bacillus spp. prevalence according to geographical continents, sources of sampling, types of dairy products, microbial species, and detection methods. The prevalence of Bacillus spp. was highest in Asia (15.4%, 95% CI: 12.3–19.1%), lowest in Oceania (3.5%, 95% CI: 3.3–3.7%) and generally higher in developing versus developed countries. The prevalence of Bacillus spp. isolated from retail markets (16.1%, 95% CI: 13.0–19.7%) was higher than from farms (10.3%, 95% CI: 6.9–15.0%) or dairy plants (9.2%, 95% CI: 7.1–12.0%). This finding is likely attributable to its inherent characteristic of the resistant endospores and ubiquitous presence in the environment—Bacillus spp. can potentially cyclically contaminate farms, dairy products and human markets. Regarding the species distribution, Bacillus cereus presented a cosmopolitan distribution across all continents. The epidemic patterns of different Bacillus species vary depending on the sample sources. In addition, the detection method utilized also affected the reported prevalence of Bacillus spp. It is recommended to use molecular-based rapid detection methods to obtain a more accurate prevalence of Bacillus contamination. Therefore, a better understanding of variations in Bacillus spp. prevalence across different factors will enable competent authorities, industries, and other relevant stakeholders to tailor their interventions for effectively controlling Bacillus spp. in milk and dairy products.